A ground book on engineering mathematics - Mukherjee, Arup Kumar (Shreedhar Prakashani, 2014)
A ground book on engineering mathematics / Mukherjee, Arup Kumar. -- Kolkata: Shreedhar Prakashani, 2014 510 M954V1 No. of Copies : 1